Estudo fitoquímico e avaliação do potencial antioxidante e antidiabético de Combretum lanceolatum Pohl. (COMBRETACEAE) - Araújo, Lais Cobianchi Junqueira (2012)
The family of Combretaceae is distributed in tropical and subtropical regions of the world, with approximately 500 species distributed in 20 genera, it is estimated the occurrence of six of them in Brazil: Buchenavia, Combretum, Canocarpus, Laguncularia, quisqualis and Terminalia, which occur in almost all vegetation formations in Brazil, as in the complex vegetation of the Amazon, Atlantic Forest, Cerrado, Caatinga and the Pantanal region. Popularly known as “Pombeiro vermelho”, Combretum lanceolatum is indicated in folk medicine in Northeast Brazil, as an infusion of his stem bark, as an aid to digestion. Phytochemical studies related to plants of this genus reported the isolation of compounds of widespread occurrence as flavonoids, tannins and pentacyclic triterpenoids, oleane and lupane skeleton specialyy, and lower occurrence compounds such as narrower combretastatins, piperidine alkaloids, flavonoids and some ammonium quaternary bases, and ciclobutanes. Many derivatives of these compounds have shown a broad spectrum of biological activities including antibacterial, anti-inflammatory, antiprotozoal, antitumor, analgesic, hepatoprotective, antidiabetic and antimalarial. Despite the importance of Combretum lanceolatum in folk medicine, nothing is known about the chemical and pharmacological properties of this species. Previous studies conducted by the Laboratory of Biochemistry UFMT aims potential results for the crude ethanol extract of flowers of C. lanceolatum, when tests were performed for antidiabetic activity. Motivated by these results and the literature describing various pharmacological activities for compounds in the genus Combretum, this paper aims, then, the isolation and identification (s) of constitutive (s) responsible (here) for the activities antidiabetic and antioxidant potential present in C. lanceolatum. The botanical material (flowers) was collected in the Poconé city and macerated with ethanol. Part of the crude extract obtained was sent to the Biochemistry Laboratory for carrying out the pharmacological tests and the remainder was divided for the realization of antioxidant activity by DPPH method and chromatographic fractionation. Studied the crude ethanol extract (EBEtOH; 2350.00 g, R = 39.43%) making up the solid-liquid partition with solvents in order of increasing polarity, resulting in Hexane (SEHex, 0.45 g R = 0.07%), dichloromethane (SEDCM; 39.52 g, 6.08%), ethyl acetate (SEAcOEt; 51.30 g, R = 7.89%) and methanol (SEMeOH; 488.00 g, 75.07%) substracts. Part of SEAcOEt (30.34 g) was subjected to fractionation on a silica column followed by Sephadex, resulting in the isolation of four flavonoids, quercetin (86.98 mg), 3-O-methyl quercetin (161.22 mg), isorhamnetin (45.90 mg) and dilenetin (136.50 mg). It’s proposals were based on structural data of IR, UV and 1H and 13C NMR. The chemical analysis of EBEtOH demonstrated the presence of the following classes of compounds: coumarins, flavonoids, resins, saponins, catechin tannins, triterpenoid and xanthones. The antioxidant potential of EBEtOH by DPPH free radical method, showed that the responsible for the high activity are the flavonoids isolated from SEAcOEt, with the same likely responsible for the antidiabetic activity of EBEtOH at a dose of 500 mg/kg in experimental model of diabetes in rats.